Identification of Genius Loci in Historical District with The Case Study of Two Alleys in Purbayan, Kotagede, Yogyakarta - Anindyta, Maheswari Rahajeng; Putri, Aulia Herlina; Agustiananda, Putu Ayu P.; Rafi , Fitri Amalia (Universitas Muhammadiyah Surakarta, 2026)
Exploring the concept of